Enhanced collaborative e-learning model with cognitive assessment and open learner model / Mahfudzah Othman and Nurzaid Muhd Zain - Othman, Mahfudzah; Muhd Zain, Nurzaid (Penerbit UiTM (UiTM Press), 2016)
This paper is focused on proposing a model of an enhanced collaborative e-learning system by including the elements of cognitive assessment and open learner model. The main objective is to provide a new andragogical tool to foster self-regulated learning for programming subjects through the online collaborative e-learning platform. The proposed model includes the cognitive assessment module in collaborative e-learning platform such as the assessment of logical thinking skills and metacognitive knowledge among the beginners in programming field. The goal is to provide the students with evaluation mechanisms towards their own cognitive abilities. The open learner model is also included in this model in order to provide qualitative performance representations to the students, where they can reflect their own milestones for each programming topic and monitor their own progress as they improve their programming skills. The open learner model will adapt the SMILI Open Learner Modeling Framework which highlights four important elements that need to be identified, which are the context and evaluation, the learners content that can be viewed, the presentations of the open learner model and the users that gain access to the system. Meanwhile, the iterative waterfall model is being proposed in this paper to be used as the overall methodology that comprises six main phases which are feasibility study, requirement gathering and analysis, design, implementation, evaluation and maintenance.